IMPACTS OF THE INDONESIAN GOVERNMENT POLICY IN THE FIELD OF DEFENSE INDUSTRY ON THE OPERATIONS AND SUPPLY CHAIN STRATEGIES OF PT. PAL AND PT DAYA RADAR UTAMA IN PRODUCING THE INDONESIAN NAVY’S MAIN WEAPON SYSTEMS - Anwar, Syaiful (Jurnal Pertahanan & Bela Negara, 2018)
Abstract - Two Indonesian companies, namely PT PAL and PT. Daya Radar Utama (DRU), have been given the tasks by the Government of Indonesia to produce several warships for the Indonesian Navy. The Government has also issued a policy in the field of defense industry, which among others regulates matters related to the procurement of the TNI’s main weapon systems. This research is intended to examine the impacts of the policy on the operations and supply chain strategies of PT PAL and PT DRU in producing warships. By using descriptive qualitative analysis method, the Researcher analyzed empirical data obtained in the field research supported by several theories, namely theory of strategy, theory of operations and supply chain strategy, theory of public policy, and theory of self-sufficient. From the analysis, there are several findings. The policies have given a certain level of positive impacts on the industries, such as: the improvement of cooperations among them, the improvement of manufacturing process due to the product’s standardization, the improvement of self-reliance level of the industries, and the capability improvement of the companies due to cooperation with foreign parties. However, the policies still give negative impacts to the companies, such as: the low level application of the supply chain management, low level use of the domestic materials and ship’s components, and the low level of fair competition among domestic defense industries.Keywords: operation strategy, supply chain, warship, PT PAL, PT DRU, Navy, Government of Indonesia, defense industry policy.